Equações de Schrödinger Semilineares com Potencial Não-Regular no Infinito - Lima, Eudes Leite de (2014)
In this work, we study issues related the existence, nonexistence and regularity of solutions to semilinear Schrödinger equations of type u + a(x)u = jujp2u; u 2 H1(RN); where N 2, p > 2 if N = 2 and 2 < p < 2N=(N 2) if N 3 and the potential a(x) is a positive function that belongs to L1(RN). To obtain the results, we use a Linking Theorem and the Principle of Symmetric Criticality.